On the high energy solitary waves solutions for a generalized KP equation in bounded domain - Rochdi, Jebari (Ukrains’kyi Matematychnyi Zhurnal, 2022)
UDC 517.9We are mainly concerned with the existence of infinitely many high energy solitary waves solutions for a class of generalized Kadomtsev – Petviashvili equation (KP equation) in bounded domain. The aim of this paper is to fill the gap in the relevant literature stated in a previous paper (J. Xu, Z. Wei, Y. Ding, Stationary solutions for a generalized Kadomtsev – Petviashvili equation in bounded domain, Electron. J. Qual. Theory Differ. Equ., 2012, № 68, 1 – 18 (2012)). Under more relaxed assumption on the nonlinearity involved in KP equation, we obtain a new result on the existence of infinitely many high energy solitary waves solutions via a variant fountain theorems.